ONLINE MEDIA COVERAGE OF ENVIRONMENTAL PROTEST IN ROMANIA. ROŞIA MONTANĂ CASE - Daba-Buzoianu, Corina (Studies and Scientific Researches. Economics Edition, 2015)
Romania, the place where protests never take place, has been facing significant civil disobedience and street demonstrations in the last years. Of them, environmental protests present several particularities and do not convey social problems. The cyanide exploitation in Roşia Montană in Romania has been debated lately due to the fact that the place is part of the Romanian historical heritage and due to the negative environment impact. The project has been delayed several times being subject to political and public environment policies. Moreover, the cyanide exploitation generated protests and street demonstrations against the project. The present study reveals the media coverage of the protest and analyses the way Romanian media referred to the environmental protest related to Roşia Montană through messages. We investigate the media message and implicitly the representation comprised in it. Our analysis includes several predetermined indicators in order to evaluate the media impact regarding the case: environment, economics, and legislative framework, presence of protests, involvement of non-governmental organizations, civil society/community and politicians.